Afroqueerness, Heteropatriarchy, and Transnationality: Nana Darkoa Sekyiamah’s The Sex Lives of African Women (Altre Modernità, 2024)
In her anthology, The Sex Lives of African Women (2021), Ghanaian writer and blogger Nana Darkoa Sekyiamah includes thirty-two stories of Black African and Afro-descendant women of different ages and sexual orientations to openly discuss queer and identity issues, family and religious dynamics, sexual freedom and pleasure, and abuses and resistance against heteropatriarchal structures. In this paper, I will first introduce Sekyiamah as a newly emerging African voice in the contemporary writing panorama and briefly examine her story collection. Second, I will discuss how gender and sex were conceived in Africa in precolonial times and how queerness and lesbianism are interpreted in the African feminist tradition. Third, I will show how Sekyiamah’s anthology can be read as a transnational Afroqueer archive by discussing some of the stories included in her volume. Significantly, I will draw on Chantal Zabus’s conceptualisation of “margins” (Zabus 31-32) to capture those spaces of free expression, openness, and resistance against colonial, nationalist, and heteropatriarchal power structures from which Afrosporic women express and manifest their often “dissenting” identities, exercise their agency, and fight for their fundamental human rights.